The Desire for Impact - Robert Dur; Amihai Glazer (Tinbergen Institute, 2004)
This paper explores the meaning and implications of the desire by workers for impact. We find that this impact motive can make a firm in a competitive labor market face an upward-sloping supply curve of labor, lead workers with the same characteristics but at different firms to earn different wages, may alleviate the hold-up problem in firm-specific investment, can make it profitable for an employer to give workers autonomy in effort or task choice, and can propagate shocks to unemployment.
Keywords: J3; J4; M5; 330; impact; monopsonistic behavior; wage differentials; hold-up problem; contracts; autonomy; Leistungsmotivation; Arbeitszufriedenheit; Leistungsanreiz; Anreizvertrag